The labor market effects of opening the border: Evidence from Switzerland - Andreas Beerli; Giovanni Peri (ETH Zurich, KOF Swiss Economic Institute, 2017)
Between 1999 and 2004 Switzerland fully opened its border region (BR) to cross-border workers (CBW), who are foreign residents commuting to Switzerland for work. In this paper, we exploit the timing of implementation and the fact that CBW commute almost exclusively to municipalities close to the border to estimate the effect of this policy on foreign labor supply and on native labor market outcomes, using a difference-in-difference approach. We find that opening the border to CBW increased their employment within 10 minutes of commuting time from the border by 4 to 5 percentage points. The increased inflow was mainly constituted of highly-educated workers and it was associated with an increase of wages of highly-educated Swiss workers and no significant changes of wages of other workers. We also find weak evidence that employment and hours worked by less educated native workers increased. Native highly-educated workers became more likely to fill top managerial positions after the liberalization and they became more likely to stay in border regions. Occupation upgrading and complementarity with highly-educated natives, particularly strong in highskilled manufacturing and knowledge-intensive services, contribute to explaining these effects of CBW on natives.
Keywords: F22; J24; J61; 330; border region; free labor mobility; policy change; cross-border workers; labor markets